Multi-Objective Decision Analytics for Short-Notice Bushfire Evacuation: An Australian Case Study - Shahparvari, Shahrooz; Chhetri, Prem; Abareshi, Ahmad; Abbasi, Babak (Australasian Journal of Information Systems, 2015)
This paper develops a multi-objective optimisation model to compute resource allocation,shelter assignment and routing options to evacuate late evacuees from affected areas to shelters.Three bushfire scenarios are analysed to incorporate constraints of restricted time-window and potential road disruptions.Capacity and number of rescue vehicles and shelters are other constraints that are identical in all scenarios.The proposed mathematical model is solved by ?-constraint approach.Objective functions are simultaneously optimised to maximise the total number of evacuees and assigned rescue vehicles and shelters.We argue that this model provides a scenario-based decision-making platform to aid minimise resource utilisation and maximise coverage of late evacuees.